Of Words and the World : Referential Anxiety in Contemporary French Fiction. - Ellison, David R. (Princeton University Press, 2001)
Here David Ellison explores the problems encountered by France's best experimental authors writing between 1956 and 1984, when faced with the question: "What should my writing be about?" These years are characterized by the rise of the "new novelists," who questioned the representational function of writing as they created works of imagination that turned in upon themselves and away from exterior reality. It became fashionable at one point to affirm that literature was no longer about the world but uniquely about the words on a page, the signifying surface of the text. Ellison tests this assum.